The Contribution of Tad?m Phenomenon to the Semantic Integrity of the Sentence in the Arabic Language - Meydanoglu, Ayse (Cumhuriyet Univ, Fac Theology, 2024)
This study deals with the contribution of the tad & amacr;m phenomenon to the semantic integrity of the sentence in the Arabic language, which is the reflection on recent studies of linguistic patterns that have been the subject of many linguistic studies from classical works to modern studies. This phenomenon is essentially a formal one that reveals the nature of the basic pattern found in different forms in all languages. Situations such as when two elements in the language require each other (istilz & amacr;m) or cannot come side-by-side (tan & amacr;fi) at all are studied within the context of the tad & amacr;m phenomenon. While the fact that each verb having an agent, and a relative pronoun (ism al-maws & umacr;l) necessitating an attributive relative clause (jumlat sila), the adjective (sifah) and the noun qualified (maws & umacr;f), the tad & amacr;m of the first (the possessor - mudaf) and the second part (the possessed - mudaf ilayh) of the possessive case are evaluated within the scope of istilz & amacr;m, the fact that the first part of the possessive case (the possessed - mudaf) cannot be a verb, a pronoun or conditional particle is discussed within the context of mutual incompatibility relationship (tan & amacr;fi). While the relationships of tad & amacr;m and istilz & amacr;m constitute the basic elements of tad & amacr;m phenomenon, the positional relationship, which necessitates the successive words to have a position in sentence syntax, is an indispensable part of tad & amacr;m phenomenon. If that position is not taken into account and violated, the sentence goes beyond the learned language patterns due to the semantic gaps that occur in the sentence. In this respect, the natural syntactic relationship between the words that constitute the sentence, or the tad & amacr;m of a word harmoniously with other words accompanying it in the sentence also falls within the scope of tad & amacr;m phenomenon. In addition, some linguists, associating the positional relationship with the concept of maq & amacr;m (the position of a word in the sentence), have made the phenomenon of tad & amacr;m suitable for evaluation within the context of rhetorical style beyond syntactic compatibility. Viewed from this angle, the phenomenon of tad & amacr;m has been given an aspect that contemporary linguists describe as the context of the situation, and in this respect, the phenomenon of tad & amacr;m provides a more semantic contribution to the sentence than the syntactic pattern. This study stands out in terms of contributing to a clearer understanding of phenomena such as hazf (omission), dhikr (mentioning), istit & amacr;r (being hidden), rutba (order of the words in the sentence), and taqd & imacr;r (underlying structure) by drawing attention to the natural pattern in the language and making the phenomenon of tad & amacr;m understandable. It is a qualitative research that tries to reveal the contribution of tad & amacr;m relationship to the semantic integrity of the sentence, and document analysis, which is one of the data collection tools, was used in it. In the data analysis phase, document analysis, and descriptive analysis techniques were used. As a result of the study, it has been found that the tad & amacr;m relationship, together with its sub-elements, provides semantic integrity in the sentence, and the sentences constructed by paying attention to this relationship constitute a more harmonious integrity semantically. It has been concluded that the tad & amacr;m relationship that provides this compatibility in the sentence involves the use of conventional and generally accepted sentence patterns with the requirements of grammar rules. Furthermore, this relation comprises also the interpretation of the wordings articulated according to the requirements of the speech situation by their position in the sentence.
Arap Dilinde Tedâmm Olgusunun Cümlenin Anlamsal Bütünlüğüne Katkısı
Keywords: Arabic Language and Rhetoric; Tad & amacr;m; & Idot;stilz & amacr;m; Tan & amacr;fi; Taw & amacr;rud